Pitfalls in methods to study colocalization of nanoparticles in mouse macrophage lysosomes - Aura Maria Moreno-Echeverri; Eva Susnik; Dimitri Vanhecke; Patricia Taladriz-Blanco; Sandor Balog; Alke Petri-Fink; Barbara Rothen-Rutishauser (Journal of Nanobiotechnology, 2022)
Abstract Background In the field of nanoscience there is an increasing interest to follow dynamics of nanoparticles (NP) in cells with an emphasis on endo-lysosomal pathways and long-term NP fate. During our research on this topic, we encountered several pitfalls, which can bias the experimental outcome. We address some of these pitfalls and suggest possible solutions. The accuracy of fluorescence microscopy methods has an important role in obtaining insights into NP interactions with lysosomes at the single cell level including quantification of NP uptake in a specific cell type. Methods Here we use J774A.1 cells as a model for professional phagocytes. We expose them to fluorescently-labelled amorphous silica NP with different sizes and quantify the colocalization of fluorescently-labelled NP with lysosomes over time. We focus on confocal laser scanning microscopy (CLSM) to obtain 3D spatial information and follow live cell imaging to study NP colocalization with lysosomes. Results We evaluate different experimental parameters that can bias the colocalization coefficients (i.e., Pearson’s and Manders’), such as the interference of phenol red in the cell culture medium with the fluorescence intensity and image post-processing (effect of spatial resolution, optical slice thickness, pixel saturation and bit depth). Additionally, we determine the correlation coefficients for NP entering the lysosomes under four different experimental set-ups. First, we found out that not only Pearson’s, but also Manders’ correlation coefficient should be considered in lysosome-NP colocalization studies; second, there is a difference in NP colocalization when using NP of different sizes and fluorescence dyes and last, the correlation coefficients might change depending on live-cell and fixed-cell imaging set-up. Conclusions The results summarize detailed steps and recommendations for the experimental design, staining, sample preparation and imaging to improve the reproducibility of colocalization studies between the NP and lysosomes. Graphical Abstract